Analysis Of Children’s Legal Protection Efforts From Parents Inmates For Children’s Emotional Health - Magnesya, Wazabrilla Artha; M. Ishaq; Eny Nur Aisyah (Institut Agama Islam Negeri Madura, 2025)
This study analyzes legal protection efforts for the emotional health of children whose parents are inmates. Using a qualitative approach with the case study method, data were collected through observation, in-depth interviews with teachers and principals, and analysis of related documents. This study uses a single subject, namely the subject in this study is only 1 child from the parents of the inmate. The results of the study showed that children with inmate parents were prone to experiencing emotional health problems, such as stress and depression. Despite child protection policies, their implementation at the local level still faces various obstacles, including a lack of resources and understanding of the specific needs of children in these situations. This study recommends increased awareness and training for educators and related parties to increase the effectiveness of legal protection and support the emotional health of children affected by their parental status as inmates.